Association of prenatal Cleft Lip and Palate ultrasound abnormalities with copy number variants at a single Chinese tertiary center - Shujuan Yan; Qiuxia Yu; Hang Zhou; Ruibin Huang; You Wang; Chunling Ma; Fei Guo; Fang Fu; Ru Li; Fucheng Li; Xiangyi Jin; Li Zhen; et al. (BMC, 2024)
Abstract Backgroud A systematic analysis was conducted to investigate the molecular etiology of fetal cleft lip and/or palate (CL/P) and the association between various types of CL/P and copy number variations (CNVs), as well as their impact on birth outcomes. Methods In this retrospective study conducted between January 2016 and July 2022, a cohort of pregnancies diagnosed with fetal CL/P was enrolled and comprehensive clinical data for all cases were extracted from our medical record database, including demographic data about the pregnancies, ultrasound findings, results of Chromosomal microarray (CMA), as well as relevant pregnant and perinatal outcomes. Results Among the 358 cases, 32 clinically significant variants in 29 (8.1%) fetuses with CL/P were detected by CMA. In 338 singleton pregnancies, the diagnostic yield of CMA in the context of CL/P fetuses was determined to be 7.7% (26/338). CP cases exhibited a relatively higher prevalence of pathogenic/likely pathogenic CNVs at a rate of 25% (3/12), followed by CLP cases at 8.0% (23/288). Notably, the CL group did not demonstrate any pathogenic/likely pathogenic CNV findings among the examined cases (0/38). The diagnostic rate of clinically significant variants was notably higher in the non-isolated CL/P group than in the isolated CL/P group (11/33, 33.3% vs. 15/305, 4.9%, p < 0.001). Within the remaining 20 twin pregnancies, three clinically significant variants (15%) were observed. Conclusions This study provides powerful evidence supporting the efficacy of CMA as a valuable tool for facilitating the prenatal genetic diagnosis of fetal CL/P. The presence of CP and CLP in fetal cases demonstrated a relatively higher incidence of pathogenic/likely pathogenic CNVs. Moreover, when these cases were accompanied by additional ultrasound abnormalities, the likelihood of identifying diagnostic CNVs significantly increased. Conversely, cases of CL alone might not be associated with positive CNVs. The present data may significantly enhance prenatal diagnosis accuracy and facilitate informed genetic counseling for cases of fetal CL/P.